MAKNA EKOLOGI BUDAYA LEKSIKON PER-UNDAGI-AN BAHASA BALI - I Putu Permana Mahardika (Program Magister Linguistik Universitas Udayana, 2019)
This research aims at describing the ecological meaning based on undagies lexicon in Balinese. The data collected by direct observation and combined with note-taking. The collected data was analyzed by applying the theory of ecolinguistics and semiotic. The lexicon used in this research were; (a) wood lexicon; (b) stone lexicon; and (c) kekarangan lexicon. Based on the analysis conducted, it was found that the undagies lexicon has an ecological meaning based on Hindus literaries such as; Aji Jan?ntaka, Asta Kosali, Asta Bhumi, and Kekawin Bhom?ntaka.